Investments in United States Government Securities by Nonfinancial Corporations, 1952-56: Reply - Minsky, Hyman P. (Quarterly Journal of Economics, 1958)
Investments in United States Government Securities by Nonfinancial Corporations, 1952–56: Reply Get access Hyman P. Minsky Hyman P. Minsky Brown University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 72, Issue 2, May 1958, Pages 297–300, https://doi.org/10.2307/1880603 Published: 01 May 1958